Classical and Molecular Cytogenetics of Disorders of Sex Development in Domestic Animals - Villagómez, D.A.F.; Parma, P.; Radi, O.; Di Meo, G.; Pinton, A.; Iannuzzi, L.; King, W.A. (Cytogenetic and genome research, 2009)
The association of abnormal chromosome constitutions and disorders of sex development in domestic animals has been recorded since the beginnings of conventional cytogenetic analysis. Deviated karyotypes consisting of abnormal sex chromosome sets (e.g. aneuploidy) and/or the coexistence of cells with different sex chromosome constitutions (e.g. mosaicism or chimerism) in an individual seem to be the main causes of anomalies of sex determination and sex differentiation. Molecular cytogenetics and genetics have increased our understanding of these pathologies, where human and mouse models have provided a substantial amount of knowledge, leading to the discovery of a number of genes implicated in mammalian sex determination and differentiation. Additionally, other genes, which appeared to be involved in ovary differentiation, have been found by investigations in domestic species such as the goat. In this paper, we present an overview of the biology of mammalian sex development as a scientific background for better understanding the body of knowledge of the clinical cytogenetics of disorders of sex development in domestic animals. An attempt to summarize of what has been described in that particular subject of veterinary medicine for each of the main mammalian domestic species is presented here.